Patients with ulcerative colitis from diverse populations: The Leicester experience. (March 2016) - Farrukh, Affifa; Mayberry, John
Background: Ulcerative colitis is common in migrant communities. There is evidence that access to care in general is impaired among such communities. The purpose of this study was to investigate whether South Asians experienced the same quality of care as English patients with ulcerative colitis. Method: The study assessed clinical care in the decade subsequent to diagnosis through a retrospective review of case notes. Newly diagnosed patients who lived in Leicester were identified and the frequency and type of consultation, in-patient admissions, surveillance colonoscopies, discharge rates, surgery and death were recorded. Results: Of 372 candidate cases identified, 70 met the criteria to be included in the study. Forty-two were of English origin and 28 South Asian. South Asian patients were significantly less likely to see a consultant and more likely to be discharged. South Asian patients were admitted to hospital more often but had significantly fewer tests than European patients. This trend was also seen in surveillance colonoscopy, although it did not reach significance. Despite these differences in the provision of care, surgical and death rates were comparable. Conclusions: Patients with ulcerative colitis who are of South Asian origin receive poorer quality clinical care than their European counterparts.